A2AR Adenosine Signaling Suppresses Natural Killer Cell Maturation in the Tumor Microenvironment - Young, Arabella; Ngiow, Shin Foong; Gao, Yulong; Patch, Ann-Marie; Barkauskas, Deborah S.; Messaoudene, Meriem; Lin, Gene; Coudert, Jerome D.; Stannard, Kimberley A.; Zitvogel, Laurence; Degli-Esposti, Mariapia A.; Vivier, Eric; et al. (Cancer research (Chicago, Ill.), 2018)
Extracellular adenosine is a key immunosuppressive metabolite that restricts activation of cytotoxic lymphocytes and impairs antitumor immune responses. Here, we show that engagement of A2A adenosine receptor (A2AR) acts as a checkpoint that limits the maturation of natural killer (NK) cells. Both global and NK-cell–specific conditional deletion of A2AR enhanced proportions of terminally mature NK cells at homeostasis, following reconstitution, and in the tumor microenvironment. Notably, A2AR-deficient, terminally mature NK cells retained proliferative capacity and exhibited heightened reconstitution in competitive transfer assays. Moreover, targeting A2AR specifically on NK cells also improved tumor control and delayed tumor initiation. Taken together, our results establish A2AR-mediated adenosine signaling as an intrinsic negative regulator of NK-cell maturation and antitumor immune responses. On the basis of these findings, we propose that administering A2AR antagonists concurrently with NK cell–based therapies may heighten therapeutic benefits by augmenting NK cell–mediated antitumor immunity. Significance: Ablating adenosine signaling is found to promote natural killer cell maturation and antitumor immunity and reduce tumor growth. Cancer Res; 78(4); 1003–16. ©2017 AACR.